Institutional investors’ effects on audit quality from a UK perspective - Simitsis, Georgios G.; Kyriakou, Maria I. (International Conference on Business and Economics - Hellenic Open University, 2025)
The monitoring role of institutional investors and its effect on audit quality stimulates further research. The UK market, a well acknowledged market with a stringent regulatory environment and significant institutional investor base, attracted our interest. The purpose of this study is to ascertain the role of institutional investors on audit quality, in a UK setting. We adopt the auditor’s opinion (modified vs unmodified) metric as a proxy for audit quality. Our empirical results support the beneficial role of institutional investors in audit quality. We also interpret the relationship of audit quality with audit fees and auditor tenure, when institutional investors are considered.Τhe relationship between audit fees and audit quality seems to be interpreted differently by institutional investors, in contrast to ordinary shareholders. Institutional investors consider audit fees as an outcome of audit effort. In this vein, increased audit fees do not seem to deter auditor independence or suppress audit quality levels. The different perspectives of institutional investors are also witnessed in the case of auditor tenure, albeit not in a statistically significant manner. While tenure is considered as an impediment to auditor independence for the whole sample, institutional investors seem to value the beneficial effects resulting from a long tenure. The empirical results add on the growing body of literature on audit quality determinants. Simultaneously, they complement research on the UK market which receives relative inattention considering its magnitude in world capital markets. JEL Classifications: M41, M42 Keywords: Audit quality, institutional investors, corporate governance, modified audit opinion, auditor independence